PENGUKURAN TEKANAN DARAH PADA PASIEN GAGAL JANTUNG KONGESTIF DI INSTALASI RAWAT INAP RUMAH SAKIT ST. ELISABETH SEMARANG - Rukminingsih, Fef; Susanto, Theresia Carolina (Jurnal Riset Kefarmasian Indonesia, 2020)
Congestive heart failure (CHF) is one of the top 10 diseases in the Inpatient of. St. Elisabeth Hospital Semarang. The main cause of CHF is hypertension. CHF patients receive antihypertensive therapy to control their blood pressure. This study aims to determine the decrease in blood pressure of CHF patients and the suitability of blood pressure of CHF patients with their treatment targets according to the Eighth Joint National Committee (JNC VIII) at the Inpatient Installation of St. Elisabeth Hospital Semarang. This research is an observational descriptive study, using retrospective data. Data was taken from medical records of CHF patients in inpatients who received antihypertensive therapy for the period October - December 2017, 40 years or older, with or without concomitant diseases. Based on the results of tracing of medical records it is known that the number of CHF patients who met the inclusion criteria was 60 people, consisting of 30 male patients and 30 female patients. A total of 35 patients (58.33%) were aged over 60 years. A total of 19 patients had concomitant diabetes mellitus type 2 and / or chronic kidney failure. A total of 51 patients (85%) during hospitalization experienced an average reduction in systolic BP of 21.65 mmHg and as many as 37 patients (61.67%) experienced an average reduction in diastolic BP of 13.38 mmHg. The suitability of the patient's blood pressure when leaving the hospital with the target blood pressure according to JNC VIII is 81.67%. Thus the progression of cardiac deterioration in most CHF patients can be inhibited.